Are the municipalities of Brussels guilty of wasteful spending? - Magali Verdonck; Michèle Taymans; Nathalie Van Droogenbroeck (Brussels Studies)
The municipalities of Brussels are often accused of being a source of financial chaos and of requiring urgent reforms. The present article attempts to objectivise the question of relative wasteful spending by the municipalities of Brussels based on a comparison of the finances of the 19 municipalities of Brussels with those of the municipalities of the four other major urban entities in Belgium: Antwerp, Charleroi, Ghent and Liege.Our methodology does not allow us to affirm that the services of the municipalities of Brussels could not be provided more efficiently. It does, however, allow us to affirm that in the case of excessive spending by the municipalities of Brussels, it would not be more than that of the other entities studied, especially if we consider the fact that the other municipalities are able to hand over part of their competences to the provinces or to a higher number of intermunicipal companies.We were not able to identify a local sector of competence with significant shortcomings, apart from the health and hygiene sector which deserves a more in-depth analysis. On the contrary, the management constraints which the municipalities of Brussels are subjected to are what clearly emerged.